Programming concurrency on the JVM : mastering synchronization, STM, and actors - Subramaniam, Venkat (Dallas, Tex. : Pragmatic Bookshelf, 2011)
"Stop dreading concurrency and start reaping the pure power of modern multicore hardware. Learn how to avoid shared mutable state and how to write safe, elegant, explicit synchronization-free programs in Java or other JVM languages, including Clojure, JRuby, Groovy, or Scala. This book is the first to show you the three prominent concurrency styles: the synchronization model of the JDK, Software Transactional Memory (STM), and actor-based concurrency. You'll learn the benefits of each of these models, when and how to use them, and what their limitations are so you can compare and choose what works best for your applications. Learning to program using concurrency is critical to creating faster, more responsive applications, and now you can leverage the Java platform to bring these applications to high-octane life."--P. [4] of cover.
The power and perils of concurrency -- Strategies for concurrency -- Modern Java/JDK concurrency -- Software transactional memory -- Actor-based concurrency.
Includes bibliographical references (p. [259]-260) and index.
Keywords: Java virtual machine; Java (Computer program language); Parallel processing (Electronic computers); Computer multitasking; Computer programming; Systems programming (Computer science)